PARTIAL ADJUSTMENT MODEL ON THE ANALYSIS OF FACTORS AFFECTING INDONESIA’S TOBACCO EXPORTS TO THE UNITED STATES - Siti Hajar Rahmawati (Jurnal Statistika Universitas Muhammadiyah Semarang, 2013)
Indonesia is having big tobacco’s production and tobacco industry also the biggest industry that hiring employee from the farmer until exporter. Researcher want to investigate the export condition next years, because the tobacco policy that imposing Indonesia lowering state farmers. This research attempt to investigate about the effect of International tobacco price on the export volume, the effect of real total GDP of the United States on the export volume, the effect of exchange rate on the export volume, and the effect of previous tobacco export. The relevance economic theory that is used is demand theory and PAM (Partial Adjustment Model) is being used as analytical method. Result show that price of tobacco and the United States real total GDP has a significant and positive effect on the volume of tobacco export. Last, tobacco export at previous year has a significant and positive effect on the volume of tobacco export. From the short-run and long-run PAM regression, conclude that Indonesia’s tobacco is less important to USA because elastic in the short-run and becoming inelastic in the future. The decision of buying Indonesia’s tobacco is induce by income it will make in the long-run the product become non-necessity. It can be concluded that Indonesia cannot rely on tobacco export and Indonesia should make product diversification or country diversification.   Keywords: PAM, Indonesian tobacco, export